دور الوساطة المصرفية والبنية التحتية في تفعيل الشمول المالي: القطاع المصرفي في الجزائر أنموذجا - بن مدخن يمينة; بوسواك امال (جامعة الوادي University of Eloued, 2024)
تسعى هذه الورقة البحثية إلى تقصي الدور الذي تؤديه البنى التحتية المصرفية و التكنولوجية في تعزيز الشمول المالي كمطلب أساسي في الجزائر، من خلال التطرق إلى تطور البنية التحتية المصرفية والتكنولوجية في الجزائر، وواقع الشمول المالي في المنظومة المصرفية الجزائرية، وانتهاءا بالبنية التحتية التكنولوجية الداعمة لنهج الشمول المالي في الجزائر، وتم استخدام المنهج الوصفي التحليلي في عرض هذه الدراسة، وتم التوصل لعدة نتائج أهممها: تطورت مؤشرات الوساطة المصرفية والعمق المالي والصلابة و مردودية القطاع المصرفي، بصفة عامة، حيث إن المنظومة المصرفية لم تستفد من البنية التحتية التقنية المتوفرة في مجال تكنولوجيا المعلومات والاتصال من أجل تفعيل الشمول المالي من خلال الاستفادة – على الأقل- من تطور نسبة المشتركين في خدمات الهاتف الثابت، والمحمول، والإنترنت، والتي تعبر بشكل ما عن مستوى الحلول الرقمية المتاحة لدعم التنمية الرقمية. This study aims to analyze the reality of financial inclusion within the Algerian banking system by examining the role of the evolution of banking intermediation and infrastructure in Algeria, in addition to the technological infrastructure supporting the activation of financial inclusion in Algeria. Employing a descriptive analytical methodology, the study draws various conclusions, predominantly highlighting the contribution of infrastructure, including the proliferation of bank branches and ATMs, in broadening the scope of financial services and enhancing accessibility to achieve banking intermediation. Nonetheless, the Algerian banking system has yet to fully leverage the available infrastructure within the information and communication technology sector. Persistent challenges impeding financial inclusion include high banking service costs, insufficient financial literacy, and inadequate infrastructure in certain regions. These obstacles can be surmounted through the implementation of supportive policies geared towards banking intermediation, infrastructure development, and financial literacy promotion.
The Role of Banking Mediation and Infrastructure in Promoting Financial Inclusion: The Case of the Banking Sector in Algeria
Keywords: الشمول المالي; الوساطة المصرفية; البنية التحتية المصرفية; النظام المصرفي الجزائري; banking infrastructure; technological infrastructure; financial inclusion